Rigid Body Dynamics Algorithm for Modeling Random Packing Structures of Nonspherical and Nonconvex Pellets - Moghaddam, Elyas M. (Ind Eng Chem Res, 2018)
[Image: see text] Despite the common use of nonspherical catalyst pellets in chemical engineering applications, the packing structures of such pellets have not been as systematically studied and characterized as spherical packings. We propose a packing algorithm based on rigid body dynamics to simulate packing of nonspherical and possibly nonconvex pellets. The algorithm exerts a hard-body approach to model collision phenomena. The novelty is that the transition between moving and resting particles is controlled by a cutoff on the relative contact velocities, instead of artificially damping linear and angular velocities to stabilize the algorithm. The algorithm is used to synthesize packings of spheres, cylinders, and Raschig rings with tube-to-pellet diameter ratios 3–9.16. The packings are validated in terms of bulk porosity and radial void fraction distribution, finding satisfactory agreement with literature data. Denser packing structures are generated with high restitution coefficients and low friction coefficients. The confining tube walls play an important role, with highly fluctuating bulk porosities in narrow tubes.